Case report: Early-onset renal failure as presenting sign of Lesch-Nyhan disease in infancy - Yang, Lianlian; Guo, Hui (Frontiers in Pediatrics, 2022)
Lesch–Nyhan disease (LND) is a rare X-linked recessive disease caused by pathogenic mutations of the HPRT1 gene. The typical clinical manifestations include cerebral palsy, intellectual disability, dysarthria, self-injurious behavior, and gouty arthritis in children. This report describes a Chinese boy aged 2 months and 7 days with a significantly elevated uric acid concentration accompanied by renal dysfunction and, notably, brain imaging changes. Whole-exome sequencing revealed a hemizygous mutation of HPRT1 in nucleotide 508 from cytosine to thymine (c.508C>T), resulting in a nonsense mutation (p.R170X). The incidence of LND is extremely low in China, and hyperuricemia is a common clinical manifestation. Therefore, the possibility of LND should be considered in children with increased uric acid in infancy accompanied by brain imaging changes or neurological dysfunction. Moreover, genetic testing is needed to provide adequate genetic counseling to the family, and should be conducted as early as possible in such children to avoid misdiagnosis or delayed diagnosis.